PERAN INVESTASI TEKNOLOGI DALAM MENINGKATKAN KINERJA KEUANGAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) 20142017 - Estu Widi Andriani (Jurnal Magister Akuntansi Trisakti, 2019)
The aimed of the research is to analyse the role of information technology (IT) investment, Operational Cost Efficiency (OCE), liquidity dan bank size through increasing financial performance in banking industries listed in Indonesia Stock Exchange period 2014 – 2017. Model that used in this study is the hypothetical testing method, that means to examine the impact of Operational Cost Efficiency (OCE), Liquidity dan Bank Size on financial performance using multiple regression method. The number of samples are 60 sample, Samples are taken by purposive sampling method. Result show that there is negative impact of OCE to financial performance, there is no impact liquidity to financial performance, there is no impact bank size to financial performance. IT investment carry out to strengthened negative relationship OCE to financial performance. On the other hand, IT investment is found unsuccessful to moderate relationship between liquidity to financial performance and bank size to financial performance.